An Empirical Study of Academic and Non-academic Staff’s Job Satisfaction and Organizational Commitment in an Institute of Higher Learning - Kok Seng, Ernest Lim Kok Seng; Wai, Cho Cho (Journal of Entrepreneurship, Business and Economics, 2016)
Numerical studies have been conducted to determine the employees’ job satisfaction and organiza-tional commitment particularly in the corporates’ settings. There are few studies pertaining to the institutional staff’s job satisfaction and organizational commitment. Therefore, this study seeks to identify the influence of job satisfaction on organizational commitment among the academic and non-academic staff in institute of higher learning. The antecedent selected to identify the organization commitment was staff’s job satisfaction. Questionnaires were constructed and distributed to the aca-demic and non-academic staff of an institute of higher learning. This study identified three important findings namely male staff were more satisfied with their jobs compared to female staff, there was no significant difference between male and female staff on organizational commitment and levels of job satisfaction has significant influence on staff’s organizational commitment. The results showed that staff who were satisfied with their jobs demonstrated higher level of commitment and more unlikely to change their job. Research paper Reference to this paper should be made as follows: Seng, E. L. K.., Choi Wai, C. (2016). “An Empir-ical Study of Academic and Non-academic Staff’s Job Satisfaction and Organizational Commitment in an Institute of Higher Learning”, Journal of Entrepreneurship, Business and Economics, Vol. 4, No. 1, pp. 45–72